(untitled) (World of finance, 2022)
Introduction. Due to the fact that monetary policy has always been the most important tool of state influence on the real sector and the dynamics of key macroeconomic indicators, the most effective monetary response of the central bank to any external shocks causing the economic crisis is necessary condition for successful economic development of each country. And as the pandemic crisis has become such a shock, both nationally and globally, the search for effective levers to offset its negative effects is among the top priorities for the monetary authorities of all countries. The experience of the US Federal Reserve in this regard is of direct practical interest given the significant developments in the modification of monetary instruments since the previous global financial and economic crisis, and therefore requires detailed study to be used to stabilize the situation and ensure proper functioning of all market mechanisms. The purpose of the article is to identify the causes and main directions of change in the practice of monetary instruments to respond to economic challenges caused by the global pandemic crisis, based on a comprehensive analysis of the experience of the US Federal Reserve as the world’s leading central bank. Results. The main aspects of the negative impact of the pandemic on the US economy, the development of which in the context of globalization significantly affects the rest of the world, and therefore the actions of the Federal Reserve to counter the effects of the crisis are of scientific and practical interest in terms of finding non-standard approaches to respond quickly to pandemic economic shocks. The objective economic reasons that determine the limitations of the regulator’s ability to apply traditional monetary policy instruments are considered and systematized. Emphasis is placed on the manifestation of the liquidity trap, which does not allow the active use of interest rate policy as a tool to stimulate economic growth. The circumstances under which the Federal Reserve was forced to actively combine traditional and non-traditional monetary policy instruments have been identified. In this regard, the whole set of measures for the Fed’s monetary response to the effects of the pandemic crisis was proposed to be classified into five areas: interest rate policy; quantitative easing; support for financial markets; intensification of bank lending; real sector support. Based on this, a strong shift in the focus of the Fed’s monetary policy towards supporting households and businesses through massive infusions of liquidity into the economy has been justified. Perspectives. As an important direction of scientific research in the near future should be considered the search for optimal ways of monetary response of central banks to manifestations of crisis phenomena, taking into account, in particular, the positive experience of the Federal Reserve System in shifting the priorities of monetary impact on the economy - from achieving certain targets of inflationary dynamics to supporting the real sector and stimulate economic growth.